Musical Input and a Multiliteracies Approach to Facilitate Intercultural EFL Learning - Fernández-García, Antonio (International Journal of English Studies, 2024)
The current multicultural context has influenced how we learn languages. On the one hand, different models of Intercultural Communicative Competence (ICC) have emerged to deal with the cultural diversity of narratives and promote heterogeneous identities. On the other, the need to consider other literacies has given rise to the incorporation of a Multiliteracies pedagogy into language learning curricula. Educators have employed numerous resources to engage students in intercultural communicative activities through this pedagogy. However, little has been analysed with respect to the effectiveness of musical input. Among the multiple reasons for its implementation is the possibility of exploring cultural contents from a critical and affective point of view. Therefore, this study seeks to propose a musical input-based approach in a multilingual EFL (English as a Foreign Language) learning context which may serve as a guide to facilitate the development of ICC through a pedagogy of Multiliteracies. Moreover, this paper aims to illustrate the applicability of musical input to facilitate intercultural EFL learning through pedagogical suggestions.